(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2016)
The uppermost Carboniferous-Lower Permian Dorud Group of the Gaduk section in Central Alborz (Iran) is more than 44 m-thick; it includes thick succession of conglomerates, quartzarenites, calcareous sandstones, oncolitic fusulinid limestones, sandy limestones, sandstones and shales. The Toyeh, Emarat and Shah Zeid formations of this Group were dated from the Gzhelian to the Sakmarian. A review of the uppermost Gzhelian, Asselian and lower Sakmarian smaller foraminifers of the Emarat Formation of the Gaduk section is here presented. Three foraminiferal biozones are defined: the Nodosinelloides shikhanica-Geinitzina primitiva Zone is latest Gzhelian in age; the Nodosinelloides spp.-Geinitzina spp.-Pseudoacutella partoazari Zone is Asselian; the Rectogordius iranicus gadukensis-Endothyra cf. bamberi Zone is early Sakmarian in age. A new subspecies Rectogordius iranicus gadukensis n. subsp. is described, and the genera Pseudovidalina and Grovesella are discussed. The studied assemblages are correlated with those from the Carnic Alps (Austria-Italy), East European Platform of Russia, the Urals (Russia), Darvaz (Uzbekistan), the northern and central Pamirs (Tajikistan), Central Iran, northern Afghanistan and other classical regions of the Tethyan realm.